Wireless backhaul: Performance Modelling and Impact on User Association for 5G. - Jaber, Mona; López-Martínez, Francisco Javier; Imran, Muhammad Ali; Sutton, Andy; Tukmanov, Anvar; Tafazolli, Rahim (IEEE, 2018)
Wireless technology is the strongest contender for catering for the 5G backhaul (BH) stipulated performance, where optical fiber is unavailable. In the presence of ultra-dense networks, such occurrences are exponentially increasing, and different wireless technologies are investigated for this application. We present the first BH-specific wireless link performance modeling that considers its inherent line-of-sight nature, together with an appropriate representation of the network topology using stochastic geometry. To this end, novel tractable models are obtained to capture the performance of wireless BH links. These are integrated into a multi-hop hybrid BH performance modeling framework and are applied in the analysis of a BH-aware user association optimisation problem.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/3585
Keywords: Sistemas de comunicaciones inalámbricos; Sistemas de comunicaciones móviles; Wireless communications; Rician channels; 5G mobile communication; Throughput; Interference; Fading channels